Transcatheter Arterial Chemoembolization Based on Hepatic Hemodynamics for Hepatocellular Carcinoma - Satoru Murata; Takahiko Mine; Tatsuo Ueda; Ken Nakazawa; Shiro Onozawa; Daisuke Yasui; Shin-ichiro Kumita (The Scientific World Journal)
Hepatocellular carcinoma (HCC) is the sixth most common cancer and the third leading cause of cancer-related deaths in the world. The Barcelona Clinic Liver Cancer (BCLC) classification has recently emerged as the standard classification system for clinical management of patients with HCC. According to the BCLC staging system, curative therapies (resection, transplantation, and percutaneous ablation) can improve survival in HCC patients diagnosed at an early stage and offer potential long-term curative effects. Patients with intermediate-stage HCC benefit from transcatheter arterial chemoembolization (TACE), and those diagnosed at an advanced stage receive sorafenib, a multikinase inhibitor, or conservative therapy. Most patients receive palliative or conservative therapy only, and approximately 50% of patients with HCC are candidates for systemic therapy. TACE is often recommended for advanced-stage HCC patients all over the world because these patients desire therapy that is more effective than systemic chemotherapy or conservative treatment. This paper aims to summarize both the published data and important ongoing studies for TACE and to discuss technical improvements in TACE for advanced-stage HCC.